Nonlinear spin waves in antiferromagnets with unixial magnetic anysotropy in a magnetic field - Gorobets, O.Yu. (Functional Materials, 2007)
It was shown in this paper that nonlinear spin waves can propagate in antiferromagnets with uniaxial magnetic anisotropy in an external magnetic field. The nonlinear waves are characterized by simultaneous oscillations of great amplitude of polar and azimuth angles of antiferromagnetism vector. It means that nonlinear wave can propagate being the exact dynamic 3D solution of Landau-Lifshitz equations in antiferromagnet. The dispersion of polar and azimuth angle oscillations are found for antiferromagnetism vector. In particular, the dispersion for oscillation of azimuth angle in a long wavelength approximation coinsides with known spin wave dispersion in antiferromagnet when the polar angle is constant. Besides, the new type of spin waves obtained in this work is characterized by possibility to form front structure at the wide class of 2D harmonic functions, possibility of two-frequency and amplitude modulation.